MO278: Immunolandscaping of Rhabdomyolysis-Induced Acute Kidney Injury. (3rd May 2022) - Rao, Snigdha; Casemayou, Audrey; Buleon, Marie; Feuillet, Guylene; Riant, Elodie; Zakaroff-Girard, Alexia; Martins, Frédéric; Gonzalez-Fuentes, Ignacio; Sébastien Saulnier Blache, Jean; Schanstra, Joost; Belliere, Julie
Abstract: BACKGROUND AND AIMS: Acute kidney injury (AKI) accounts for 13.3 million cases per year worldwide and further responsible for 1.7 million deaths per year [1]. Increasing incidence of AKI, progression toward CKD or end-stage renal disease (ESRD), affect on long term health, high mortality, morbidity and high costs are all accountable for the need to analyze AKI at a closer level [2]. Rhabdomyolysis (RM) accounting for 10% of AKI cases is due to damage of the skeletal muscle causing a release of muscle cell contents like myoglobin and toxins into the bloodstream leading to AKI, renal failure and possibly death. RM-induced AKI (RIAKI) occurs due to a variety of causes like fall risk, exposure to drugs, infections, muscle hypoxia, infections, body-temperature changes and metabolic and electrolyte disorders [3]. The immune system has been reported to play a role in the pathogenesis of AKI through inflammatory pathways. Macrophages are known to be involved in AKI to CKD transition [4]. Macrophages play an important role in the pathogenesis of RIAKI. While macrophage subtypes (inflammatory type) have been reported to drive RIAKI lesions and prognosis [5], the role of the other immune cells needs to be explored. The aim of this study was to analyze the recruitment of the whole immune system during RIAKI through single-cell RNA sequencing. METHOD: Two month old C57BL/6J male mice were used for this study. Mice were administered saline (control) or glycerol i.m (7.5 mL/kg 50% glycerol diluted in saline) for induction of RM. Mouse tail vein blood was collected at 6, 24 and 48 h and serum was obtained after centrifugation (5 min at 2000 rpm). Biochemical analysis tests were used to evaluate RM intensity (creatinine phosphokinase, CPK) and renal function (blood urea nitrogen, BUN) using a Pentra 400 analyzer. To analyze the immune cell recruitment in kidney, kidneys from control and glycerol treated mice were decapsulated, minced and incubated with collagenase and DNase. The dissociated cells were then incubated in red cell lysis buffer and passed through a 40 µm filter. The dissociated cells were further incubated with CD45 antibodies and a viability marker. Kidney CD45 live cells were sorted using BD Influx cell sorter. Preparation of single cell libraries was done and single-cell RNA sequencing was performed according to 10× Genomics protocol. RESULTS: Eight clusters (macrophages, monocytes, endothelial cells, neutrophils, natural killer T cells, B cells, T cells and dendritic cells) were revealed after single-cell RNA sequencing of CD45 + renal cells. Recruitment of macrophages, monocytes and neutrophils were revealed to be modified by RIAKI. As expected, NF-kB signaling pathway was the major pathway upregulated in multiple clusters. Pathway analysis in T cell cluster showcased T cell selection and differentiation and T cell receptor signaling pathway. AA467197 (a long non-coding RNA which has been reported in renal ischemia–reperfusion) was upregulated through differential expression analysis in multiple clusters. Macrophage subclustering revealed a high macrophage diversity in the seven macrophage subclusters that shared markers for macrophage subtypes (M1, M2) and pro-inflammatory markers. KLf9 was upregulated in cluster 7, which has been reported to be a stress-responsive gene associated having pro-inflammatory effect. NF-kB and IL-2 STAT5 signaling pathways were the major pathways upregulated in multiple clusters. Drug repositioning studies with connectivity map showcased SRC inhibitions as potent pharmacological intervention strategy. CONCLUSION: This study revealed the immune landscaping and pathways associated in RIAKI. Single-cell approach illustrated macrophages diversity in pathological context and suggested candidates for further therapeutic approaches.